Nitrogen-carbon graphite-like semiconductor synthesized from uric acid. (September 2017) - Dante, Roberto C.; Chamorro-Posada, Pedro; Vázquez-Cabo, José; Rubiños-López, Óscar; Sánchez-Árevalo, Francisco M.; Huerta, Lázaro; Martín-Ramos, Pablo; Lartundo-Rojas, Luis; Ávila-Vega, Carlos F.; Rivera-Tapia, Edgar D.; Fajardo-Pruna, Cristian A.; Ávila-Vega, Álvaro J.; et al.
Abstract: A new carbon-nitrogen organic semiconductor has been synthesized by pyrolysis of uric acid. This layered carbon-nitrogen material contains imidazole-, pyridine (naphthyridine)- and graphitic-like nitrogen, as evinced by infrared and X-ray photoelectron spectroscopies. Quantum chemistry calculations support that it would consist of a 2D polymeric material held together by hydrogen bonds. Layers are stacked with an interplanar distance between 3.30 and 3.36 Å, as in graphite and coke. Terahertz spectroscopy shows a behavior similar to that of amorphous carbons, such as coke, with non-interacting layers. This material features substantial differences from polymeric carbon nitride, with some characteristics closer to those of nitrogen-doped graphene, in spite of its higher nitrogen content. The direct optical band gap, dependent on the polycondensation temperature, ranges from 2.10 to 2.32 eV. Although in general the degree of crystallinity is low, in the material synthesized at 600 °C some spots with a certain degree of crystallinity can be found. Graphical abstract: